Blockchain-enhanced vehicle data management system with file-based search for crime detection - Sim, Chul Jun (Edelweiss Applied Science and Technology, 2025)
Effective vehicle data management is crucial for traffic safety and public security, requiring both rapid processing and robust security mechanisms. This study presents a hybrid system that combines a file-based search algorithm with blockchain technology to improve performance and security. The file-based search algorithm facilitates quick data retrieval, while blockchain ensures data integrity and protects against tampering. By integrating these two methods, the system overcomes common bottlenecks and security vulnerabilities found in centralized architectures. Experimental results reveal that the proposed system enhances data processing speed by 84%, considerably increasing data security. These findings highlight its practical applications in smart cities, traffic management, and public safety.